Characterisation of biochar porosity from pyrolysis of biomass flax fibre. (1st May 2013) - Illingworth, James; Williams, Paul T; Rand, Brian
<x xml:space="preserve">Abstract</x> Low grade biomass fibre produced as a byproduct from the flax industry was manufactured into a non-woven fabric. This material was then pyrolysed in a fixed bed reactor to produce biochar. The resulting biochars were characterised using a variety of techniques including gas adsorption, scanning electron microscopy, pychnometry and elemental and proximate analyses. The fibrous morphology of the precursor was retained during pyrolysis. The temperature of pyrolysis had a significant influence on the biochar properties, with higher temperatures causing an increase in surface area and density along with a decrease in volatile/disorganised carbon. All of the biochars were microporous, with the majority in the ultramicropore size range. Activated diffusion effects were observed during nitrogen adsorption measurements at 77 K. The experimental data show that the flax biochars exhibit properties typical of biochars produced from other lignocellulosic precursors.